Influence of coach behaviour on motivation in swimming - a systematic investigation - Staub, I.; Bieder, A.; Ufermann, L.; Vogt, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION High-performance swimming requires extensive training loads (Maglischo, 2015), often characterized by monotony and isolation. It requires persistence and commitment to develop performance and eventually be successful in elite swimming. Therefore, motivation plays an essential role. The coach is the athlete's most important reference and influences athletes` motivation (Mageau & Vallerand, 2003). This systematic review investigates the influence of coaching behaviors in the motivational context of competitive swimming.